Extending Public Health: The Rockefeller Sanitary Commission and Hookworm in the American South - Elman, Cheryl (American Public Health Association, 2014)
The Rockefeller Sanitary Commission for the Eradication of Hookworm Disease (1909–1914) fielded a philanthropic public health project that had three goals: to estimate hookworm prevalence in the American South, provide treatment, and eradicate the disease. Activities covered 11 Southern states, and Rockefeller teams found that about 40% of the population surveyed was infected. However, the commission met strong resistance and lacked the time and resources to achieve universal county coverage and meet project goals. We explore how these constraints triggered project changes that systematically reshaped project operations and the characteristics of the counties surveyed and treated. We show that county selectivity reduced the project’s initial potential to affect hookworm prevalence estimates, treatment, and eradication in the American South.